Opportunities of Arts Education in Implementing Inclusive Education: Learning Experiences of Teachers in the International Context - Strakšienė, Diana; Musneckienė, Edita (Special Education, 2024)
The article analyzes the relevance of arts education and teachers’ professional development while implementing inclusive education. The background for this article is an evaluation of an international in-service teachers’ training program focusing on inclusive arts education. This study aims to investigate what inclusive education means to arts teachers and reveal their learning experiences in the international training program “Inclusive Arts Education”. The qualitative research was conducted using the focus group method with international training program participants from three different European countries (Finland, Austria and Lithuania). The study involved 25 participants: 7 from Finland, 7 from Austria and 11 from Lithuania. The research has shown that in each country arts teachers work in different national and educational contexts but face quite similar challenges of inclusive education. The success of inclusive art education mainly depends on the teacher’s professional abilities and attitude towards inclusion, as well as the creation of a favourable educational atmosphere and positive relationships with students in the educational process. The experience of the research participants highlighted their attitudes to the content and organization of international training, which will help to develop continuing education programs for arts teachers’ preparation for inclusive arts education.